Antiprotozoan and Antiviral Activities of Non-cytotoxic Truncated and Variant Analogues of Mussel Defensin - Roch, Philippe (Oxford University Press, 2004)
We previously reported the crucial role displayed by loop 3 of defensin isolated from the Mediterranean mussel, Mytilus galloprovincialis, in antibacterial and antifungal activities. We now investigated antiprotozoan and antiviral activities of some previously reported fragments B, D, E, P and Q. Two fragments (D and P) efficiently killed Trypanosoma brucei (ID(50) 4–12 μM) and Leishmania major (ID(50) 12–45 μM) in a time/dose-dependent manner. Killing of T. brucei started as early as 1 h after initiation of contact with fragment D and reached 55% mortality after 6 h. Killing was temperature dependent and a temperature of 4°C efficiently impaired the ability to kill T. brucei. Fragments bound to the entire external epithelium of T. brucei. Prevention of HIV-1 infestation was obtained only with fragments P and Q at 20 μM. Even if fragment P was active on both targets, the specificity of fragments D and Q suggest that antiprotozoan and antiviral activities are mediated by different mechanisms. Truncated sequences of mussel defensin, including amino acid replacement to maintain 3D structure and increased positive net charge, also possess antiprotozoan and antiviral capabilities. New alternative and/or complementary antibiotics can be derived from the vast reservoir of natural antimicrobial peptides (AMPs) contained in marine invertebrates.